Selective Flotation of a Copper-molybdenum Bulk Concentrate from Xizang - Jinming GUO; Hongying YANG; Shiqi ZHANG; Linlin TONG; Zhenan JIN; Qin ZHANG (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering. A technological mineralogical study was carried out on a copper-molybdenum bulk concentrate in Xizang. Studies have shown that the copper-molybdenum bulk concentrate contains 19.00% Cu and 0.38% Mo, and the grade of molybdenum is relatively low. The main reasons for this are the low separation efficiency of copper and molybdenum and the poor quality of molybdenum concentrates. The optimal grinding fineness, pulp concentration and agent system are determined through condition tests: the mixed concentrate is not ground, that is, the particle size -0.045 mm accounts for 67.87%, the pulp concentration is 40%, and the mixed inhibitor sodium hydrosulfide: sodium thioglycolate=2.5:1. The dosage of mixed inhibitor is 5 000 g/t, sodium silicate is 1 500 g/t, kerosene is 80 g/t, pinitol oil is 24 g/t, AT208 300 g/t is added in the third step, and the fourth step is added scrubbing process. After one roughing separation, seven cleaning separations and two scavenging swparations of the closed-circuit test, the finally obtained molybdenum concentrate contains 46.50% molybdenum, 0.94% copper, and the recovery rate of molybdenum is 80.76%, the copper concentrate contains 19.12% copper and 0.07% molybdenum, and the recovery rate of copper is 99.97%, and copper and molybdenum achieved good separation.